Synthesis and Evaluation of a Chitosan–Silica-Based Bone Substitute for Tissue Engineering - Alvarez Echazú, María Inés (2022)
Bone defects have prompted the development of biomaterial-based bone substitutes for restoring the affected tissue completely. Although many biomaterials have been designed and evaluated, the combination of properties required in a biomaterial for bone tissue engineering still poses a challenge. In this study, a chitosan–silica-based biocomposite was synthetized, and its physicochemical characteristics and biocompatibility were characterized, with the aim of exploring the advantages and drawbacks of its use in bone tissue engineering. Dynamic light scattering measurements showed that the mean hydrodynamic size of solid silica particles (Sol-Si) was 482 ± 3 nm. Scanning electron microscopy of the biocomposite showed that Sol-Si were homogenously distributed within the chitosan (CS) matrix. The biocomposite swelled rapidly and was observed to have no cytotoxic effect on the [3T3] cell line within 24 h. Biocompatibility was also analyzed in vivo 14 days post-implant using a murine experimental model (Wistar rats). The biocomposite was implanted in the medullary compartment of both tibiae (n = 12). Histologically, no acute inflammatory infiltrate or multinucleated giant cells associated to the biocomposite were observed, indicating good biocompatibility. At the tissue–biocomposite interface, there was new formation of woven bone tissue in close contact with the biocomposite surface (osseointegration). The new bone formation may be attributed to the action of silica. Free silica particles originating from the biocomposite were observed at the tissue–biocomposite interface. According to our results, the biocomposite may act as a template for cellular interactions and extracellular matrix formation, providing a structural support for new bone tissue formation. The CS/Sol-Si biocomposite may act as a Si reservoir, promoting new bone formation. A scaffold with these properties is essential for cell differentiation and filling a bone defect.